Crystal structure and molecular packing of O-ethyl (2-chlorophenyl)carbamothioate, C9H10ClNOS - Yeo, Chien Ing *; Tiekink, Edward R. T. * (de Gruyter Open Access, 2018)
The asymmetric unit of the title crystal structure is shown in the figure. Tables 1 and 2 contain details of the measurement method and a list of the atoms including atomic coordinates and displacement parameters.